Taxonomy of the genus Duolandrevus Kirby, 1906 (Orthoptera: Gryllidae; Landrevinae) from China with a new species of the subgenus Eulandrevus Gorochov, 1988 - Zheng, Yanna; Ma, Libin (Zootaxa, 2021)
Duolandrevus species are brown, smooth and shiny, and armed with short tegmina. There are twelve species recorded from China. We redescribed five species of them and reported a new species, Duolandrevus longlouensis sp. n., discovered in Hainan Island, China. The new one belongs to the subgenus Eulandreus and is similar to Duolandrevus obsidianus He, 2019 and Duolandrevus dendrophilus (Gorochov, 1988), but differs from them in body size and details of tegmina and genitalia. Besides description and illustration of the five recorded species and one new species, keys and distribution map of Chinese bark crickets were provided.